Political and Transitional Justice in Germany, Poland and the Soviet Union from the 1930s to the 1950s - Zarusky, Jürgen 1958-2019 (Wallstein Verlag, 2019)
Focussing on »Political and Transitional Justice in Germany, Poland the USSR from the 1930s to the 1950s« this volume presents papers organized by the editors to demonstrate the importance of cooperation in research beyond national borders. The articles reflect the need for constant awareness of the challenges of Political Justice as a topic not just of historical importance but with relevance to present-day negotiations of the past